Environmental Assessment of the Greenhouse Gases’ Emission from Poultry Production in Russia’s Central Region - Samardžić, Miljan; Vasin, Jovica; Jajić, Igor; Andreeva, Irina V; Latković, Dragana; Vasenev, Ivan I (Journal of Agricultural Sciences (Belgrade), 2018)
Summary: With estimated rise in poultry production and consumption of chicken meat in Russia for 9% up to 2022, as well as development of self-sustainable poultry production, the need has arisen for environmental assessment of this production, and within it especially greenhouse gases (GHG) emission assessment. The goal of this work is to show a calculation procedure for obtaining estimations for the Carbon footprint of the 1 kg of live chicken at the farm gate, taking into account regional typological features of agricultural production in agro-ecosystems. The methodology of Carbon footprint (CF) calculation is based on the life cycle assessment (LCA) methodology, and on IAGRICO2 calculator, developed for agriculture products. Results had shown that in modern, 42 days long technology of poultry farming, 5,79 kg CO2 е is emitted in average per kg of body mass, and that about 47% of emission is from manure, around 27,5% from crop production (fuel and fertiliser) and 25,5% from fuel and energy needed for heating, sanitation and feeding of chickens. The main distinction of Central Russia is low efficiency of the fertiliser application on crop fields and manure management, storage and  utilisation, which has as a result high emissions of the nitrous oxide. This is the field where the implementation of the intensive technologies of precise farming, manure handling, utilisation and management will significantly decrease GHG emission, with preserving yield of crops and quantity and quality of chicken meat. Key words: greenhouse gases, poultry, manure, energy, fertilisers, agro ecosystems, carbon footprint